Verification of measurement possibilities of quasi-continuous acoustic wave packets for technical and medical applications - Szustakowski, M.; Jodłowski, L.; Piszczek, M. (Archives of Acoustics, 2001)
Quasi-continuous acoustic wave packets are used for investigations of real objects due to determination of their material parameters such as, for example, propagation velocity of an acoustic wave, or localisation of their inner structures. Application of low sampling frequencies (500kHz) in comparison with the strict harmonic probing signals [ampersand]sim;1.5MHz offers very promising measuring possibilities (detection of the transit time changes of acoustic signal [ampersand]asymp;5ns). This paper shows the test measurement results for a glass vessel (300mm probing path in distilled water) and patients with pathological changes (ischemia and internal haemorrhage in the brain tissue) using the phase and time methods. High sensitivity of measurements ensures detection of differences in density of the order of [ampersand]sim;3[ampersand]middot;10-3kg/m3, propagation velocity of acoustic wave [ampersand]sim;4[ampersand]middot;10-2m/s, temperature [ampersand]sim;1.5[ampersand]middot;10-2K and change of the acoustic path [ampersand]sim;4[ampersand]mu;µm. Sensibility and simplicity of the measuring system makes the proposed solution a very attractive tool for investigations. It can be applied for measurement of different changes of the material properties in the automatic systems and medicine.